(untitled) (Journal of Philosophy Culture and Political Science, 2018)
The article analyzes the problems of interaction between the government and the society in the condition of globalization. The effective cooperation between them and increasing the quality of this interaction is in the agenda of all the nations in the world. The effective cooperation between the government and society, as well as its optimization in compliance with the new changes was underlined in the Address of the President of Kazakhstan Nursultan Nazarbayev to the Kazakhstani nation entitled “The Kazakhstan-2050 Strategy: a new political direction of the established state”. This will be the main factor of Kazakhstan’s entering into the list of most developed nations in the world, and it will determine all the spheres of its development strategy till 2050. The article describes the possible challenges to this interaction and the ways of addressing them. Key word: power, political power, state, policy, civil society, democracy, modernization, Republic of Kazakhstan, political parties, message, Kazakhstan People’s Assembly, opposition, strategy, civic Alliance